Nurses in emotional competence: exploratory study on population of continued care national network - Lopes, Tânia Santos (2014)
The relevance of this study - the first empirical research (to our knowledge) in Continued Care National Network (RCNN) context - emerge to understand the role of emotions in workplace behaviour (Côté, 2005; Austin, Dore & Donovan, 2008; Liu et al. 2008; Barsade, Ramarajan, Burack, 2008), but here, with terminally ill people and great physical and psychological weakness. Recent scientific literature is exposing a significatly negative correlations between Emotional Intelligence (EI) and emotional exhaution; and significantly positive correlations between EI and occupational identity (Geng; Li; Zhou, 2011), and the development of emotional competence (EC) skills in workplace context (Veiga-Branco, 2007, 2010, 2011). Authors agree with the relationship between emotional responses, therapeutic relationship and perception of job satisfaction (Li, 2004; Hart & Walton, 2010; Karim & Weiz, 2010). Keywords: emotional inteligence, emotional competence profile, nurses Aim: to know, the capacities levels in the Emotional Competence (EC) profile in a nurses sample of RNCC, and study the five capacities as predictive variables, in the their Emotional Competence’s (EC) profile. Method:A cross-sectional survey was carried out in a probabilistic sample including 154 nurses in RNCC, about 22 % male and 78% female, and aged between 26 and 30 years old. The instrument applied was “Escala Veiga de Competência Emocional” (EVCE), developed by Veiga-Branco (2009), with 84 itens, in temporal Lickert scale, from Never (1) to Always (7). Data was analyzed using descriptive statistics. Factor analysis was used to identify capacities. Additionally, a multiple regression analysis was conducted to determine the relationship between capacities and EC and to establish the capacities that were the strongest predictors of EC. Conclusions/Results : 1. Five competencies were identified in this study. The ranking of the correlations was as follows: Empathy (r=0.783; p<0.01), Emotions Management in Group (r=0.724; p<0.01), Emotions Management (r=0.760; p<0.01), Self-motivation (r=0.693;p<0.01), and Self-conscience (r=0.678; p<0.01). The results were according the American Society of Registered Nurses (2007) that emphasizes the need of emotional skills in nursing education. 2. The Cronbach Alpha for Internal Consistency obtained for each of the capacities was as follows: Empathy (0.854), Emotions Management in Group (0.833), Emotions Management (0.740), Self-motivation (0.705), and Self-conscience (0.622). 3. The estimated regression model includes Empaty, Emotion Management, Self- Motivation, Emotions Management in Group, Self-conscience, that represents 97,4% of the variance in EC. This result, not according the theoretical model (Caruso & Salovey,2004), presents how much important is empathy in work settings.